DESIGN OF EARTHQUAKE RESISTANT STEEL MOMENT FRAME ON MULTI-STORY BUILDING - Rianto, Shandy
The geographical condition of Indonesia which is located in an area surrounded by the Ring of Fire and is located between where large and active plates meet makes Indonesia prone to earthquakes. In addition, limited land drives the development in Indonesia towards the construction of multi-story buildings. Therefore, the design of multi-story earthquake resistant buildings is an important aspect to minimize the losses due to earthquakes. In this final project, the design of the multi-story building is carried out for steel structures by considering the advantages and challenges of steel structures. The structure designed in this final project is a multi-story building with a realistic and commonly found in the field structure plan. The structure consists of 8 stories with a height of 4 m on the base story and 3.5 m for the stories above. The structure consists of 4 spans in the X direction with a span length of 6 m and 6 spans in the Y direction with a span length of 5 m. The building will be functioning as office and is assumed to be located in the location of BATAN (Badan Tenaga Nuklir Nasional) Bandung. Earthquake forces analysis is based on response spectrum analysis procedure. The structure is designed according to SNI 1726:2018 for the design of earthquake resistant structures, AISC 360-16 for the design of steel structures, and AISC 341-16 for the seismic requirement of steel structures. The design is carried out for two types of earthquake force resisting systems, which are special moment frame and ordinary moment frame.